ABU NAWAR: TOKOH PEMBUDIDAYA TANAMAN GAHARU DI NAGARI PADANG LAWEH KECAMATAN KOTO VII KABUPATEN SIJUNJUNG 2011-2022 - Zulfahmi Zulfahmi; Hendra Naldi (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This research is one of the historical studies that discusses the biography of Abu Nawar as a figure cultivating agarwood in 2011-2022. The purpose of this study is to describe Abu Nawar's business and the situations and conditions he faced in cultivating gaharu plants and to explain the success of Abu Nawar in developing the cultivation of gaharu plants into a traditional drink in the form of gaharu tea which has been tested in labor. This research uses historical research methods with the following steps: (1) Data collection heuristics as Primary Sources Interviews with relatives of figures, work members, neighbors and the surrounding community and Secondary Sources conducts a search of data from relevant books and related agencies . (2) Source Criticism, both internal and external. (3) Data interpretation and (4) Historiography, describing research results in the form of scientific writing, namely articles. The results of this study indicate that while Abu Nawar was cultivating gaharu plants in Nagari Padang Lawas, Koto VII District, Sijunjung district, he experienced developments both at the provincial and national levels.Â